Jockey [videorecording (DVD)] - Collins, Clifton, Jr; Parker, Molly, 1972-; Arias, Moises, 1994- (Sony Pictures Home Entertainment, 2022)
An aging jockey aims for a final championship, when a rookie rider arrives claiming to be his son.